Trajetos formativos na EBPT: significações imaginárias de docentes LGBT - Biazus, Paula Hosana Silveira (2020)
This dissertation presents a research done with seven teachers, which aimed to know the training paths of LGBT teachers, from Basic Technical and Technical Education (EBPT), in order to analyze repercussions in their pedagogical practices. We sought to know their training paths and discuss how they recognized themselves, where they believed they had learned to be teachers. It was also intended to understand under what imaginary meanings of teaching their actions were based and the possible relations with their professional autonomy. In addition, we tried to understand the repercussions of these images in their pedagogical practices. For this, the methodological choice was qualitative and exploratory. The snowball methodology was chosen because it facilitates and promotes contact with the interviewees, who, upon indication of other possible interviewees, now named as 'seeds' for the accomplishment of the interview, made this work possible. The inclusion criteria were LGBT self-identification and having exercised or have been exercising the teaching profession in an EBPT institution for at least two years. As for the production of data, we opted for interviews as a semi-structured type, which were expanded with the dialogues that occurred with teachers, according to the comfort of each one in response to our questions. For data analysis, Content Analysis of the Thematic Categorical type was the one that had been used. It was possible to notice that despite their academic backgrounds, episodes of explicit or veiled prejudice also occurred, even within their work spaces, demanding our attention to a more effective discussion about the influences of the personality and the imaginary, also, at professional environments. About the possible specificity of the pedagogical practices of LGBT teachers, we approach the concept of empathy and the need for further discussions on those subjects, understanding that this approach is not due to the sexual orientation of the participants at this research, but because of the experiences they have experienced through self-identify as LGBT.